Reducing Employee Turnover Intention through Compensation, Support, and Engagement in Indonesia: Mengurangi Niat Keluar Masuk Karyawan melalui Kompensasi, Dukungan, dan Keterlibatan di Indonesia - Sahid, Ahmad; Firdaus, Vera (Indonesian Journal of Law and Economics Review, 2024)
This study investigates the impact of compensation, organizational support, and work engagement on turnover intention at PT. Nugraha Ekakurir Line (JNE) Sidoarjo. Using a quantitative, descriptive method, data was collected via questionnaires from 114 respondents and analyzed with SPSS version 26. The results show that compensation, organizational support, and work engagement each have a negative and significant partial effect on turnover intention, and together they have a significant simultaneous effect. These findings suggest that enhancing compensation, organizational support, and work engagement can effectively reduce employee turnover. Highlight: Compensation, organizational support reduce turnover intention. Data from 114 respondents analyzed using SPSS 26. Enhancing these factors minimizes employee turnover. Keywoard: Compensation, Organizational Support, Work Engagement, Turnover Intention, Quantitative Study